Análise das métricas da W3C para o desenvolvimento de sítios destinados a eventos acadêmicos. - Santos, Samuel Silva dos (2023)
The growing importance of accessibility in web systems is noteworthy. This is attributed to technological advancements, the expansion of internet usage, population growth, among other factors. Faced with the need to make systems accessible to all individuals, regardless of special needs, this study aims to contribute to accessibility in websites for academic events, relying on the recommendations of the Web Content Accessibility Guide from the World Wide Web Consortium. Consequently, an evaluation of the website for an annual academic event within the higher education institution is conducted through a web tool. The results revealed challenges in areas such as images, links, and contrasts, indicating that the pages do not comply with accessibility guidelines. The identification of key issues and improvement suggestions underscores the urgent need to adapt the website to comply with legislation and promote the inclusion of individuals with visual impairments. Therefore, this study emphasizes the ongoing relevance of effectively implementing accessibility guidelines to contribute to digital inclusion.